2018
DOI: 10.1007/s11033-018-4564-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis reveals the mechanism of Musa paradisiaca responding to salt stress

Abstract: Salinity is one of the most important abiotic stresses, which affects the yield and quality of banana (Musa paradisiaca). To understand the salinity tolerance mechanisms of banana, the iTRAQ technique is employed to reveal the proteomic response of Brazil banana under different durations of 60 mmol/L NaCl stress. We have identified 77 DEPs and classified them into nine functional categories, compared with control (0 mmol/L NaCl treatment). The four major categories involve protein synthesis and degradation, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…3). Increased abundance of peroxidase under salinity stress was also reported in roots of many different plant varieties including banana, radish and barley (Ji et al, 2019, Witzel et al, 2014 indicating it's a common response of plant roots. Significant increase of abundance of O-methyltransferase, glutathione-S-transferase and phenylalanine ammonia lyase detected by un-targeted proteome profiling analysis in root tips indicates the active production of secondary metabolites to cope with salt stress (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…3). Increased abundance of peroxidase under salinity stress was also reported in roots of many different plant varieties including banana, radish and barley (Ji et al, 2019, Witzel et al, 2014 indicating it's a common response of plant roots. Significant increase of abundance of O-methyltransferase, glutathione-S-transferase and phenylalanine ammonia lyase detected by un-targeted proteome profiling analysis in root tips indicates the active production of secondary metabolites to cope with salt stress (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we found that hypersensitive-induced response protein 1 (HIR1) was suppressed in BE, while hypersensitive-induced response protein 4 (HIR4) was expressed in OG only ( Table S10 ). Previous reports have found that putative hypersensitive-induced proteins were upregulated in banana, Halogeton glomeratus , and coconut leaf proteomic analysis under salinity and low-temperature stress [ 6 , 71 , 72 ]. There is a possibility of synchronizing the response of plants to various stimuli, including abiotic and biotic stresses [ 73 ], and oil palm-led proteomic analysis under low-temperature stress could be involved in multi-stress responses such as biotic, abiotic, heat shock, and oxidative stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 82 significantly affected proteins, the largest group were assigned to the category "stress", of which eight were downregulated, and 19 were upregulated under salinity conditions. Several of these proteins are known to be involved in salt and drought stresses (non-specific lipid-transfer protein, inorganic pyrophosphatase 2, 60 kDa jasmonate-induced protein) [20][21][22] and pathogenic stress and other biotic stresses (proteins germin-like) [23].…”
Section: Differentially Abundant Proteins In Response To Salt Treatmementioning
confidence: 99%